Advanced Assistive Technologies for Elderly People: A Psychological Perspective on Seniors' Needs and Preferences (part A) - Vogel, Carl (My University, 2020)
This paper provides an overview of the literature concerning Seniors’ psychological perspective in exploiting assistive robots and the embodied conversational agents. The main theoretical models devoted to assess user’s technology acceptance are briefly reviewed along with a description of the main factors empirically found to be positively/negatively associated with Seniors’ acceptance level. Special attention is reserved to barriers generated by Seniors’ representations of social assistive technologies, such as, a stigma or threat to their autonomy, infantilization, privacy interferences, fear of dehumanization and isolation.
PUBLISHED
Keywords: Older user; Assistive technology; Robot; Virtual agent; Acceptance; Preferences; Ageing; Digital Engagement; Digital Humanities; AGEING; ASSISTIVE TECHNOLOGY; Ageing, Older People and Healthcare; Computational Linguistics; Computational linguistics; Positive Ageing; computational linguistics